More money does not necessarily help: relations of education expenditure, school characteristics, and academic resilience across 36 education systems - Ye, Wangqiong; Olsen, Rolf V.; Blömeke, Sigrid (Frontiers in Education, 2024)
Teacher quality, teaching quality, school resources, and school climate are commonly identified as protective factors in the academic resilience literature. Variables reflecting these four concepts were applied in a latent profile analysis across 36 education systems participating in the Trends in International Mathematics and Science Study 2019. The best-fitting model suggested four different latent profiles of protective factors. A three-step BCH method with an auxiliary regression model was adopted to investigate the influence of education expenditure on academic resilience across the profiles. Education expenditure promoted academic resilience in a profile characterized by low mathematics resources and another profile with low teaching quality and school climate. Education expenditure had no significant influence in the remaining two profiles characterized by very low and high levels of classroom and school protective factors, respectively. Moreover, countries were classified into six cultural groups representing education systems sharing similarities in language, history, or geography. Within each group, there was a certain degree of consistency in the distribution of profiles. Conclusions are drawn for strategies to promote academic resilience.